A review on physical, mechanical, thermal properties and chemical composition of plant fibers - Norliana, Bakar; Chin, Siew Choo; Siregar, J. P.; Ngien, S. K. (IOP Publishing, 2020)
In recent years, research on natural fiber composites increased owing to their lightweight, easy availability and improved mechanical characteristics. Natural fiber is also an environmentally friendly material, which produces less pollutant during its production. Therefore, extensive research has been carried out on natural fibers as they constitute an interesting alternative to traditional synthetic fibers, especially for composite materials. This paper presents a comprehensive review on the physical, mechanical and thermal properties as well as chemical composition of natural fibers. Comparison between different natural fibers regarding the aforementioned properties and composition are presented and discussed. This review will provide a useful guide on the performance of natural fibers in natural fiber reinforced composites for other applications such as structural strengthening.